Produksi enzimatis Virgin Coconut Oil (VCO) dengan enzim bromelin serta pemurniannya menggunakan adsorben zeolit - Septiany Christin Palilingan; Meity Pungus (Jurnal Kimia Fullerene, 2018)
One of the processed coconut products that is beneficial to health and has been widely used as an industrial raw material is VCO. Traditional rural communities and households have produced their own VCO for personal consumption because of its health benefits. However, the production process of VCO which still traditionally produces VCO products with a standard of quality and yield that has not been maximized. The research was carried out by enzymatic method, which added the enzyme bromelain contained in pineapple stem extract into coconut milk. The VCO product obtained was then purified by zeolite adsorbent, and water content and free fatty acid levels were tested. The results showed the highest VCO yield was found at a concentration of 20%, which was 36% and the purification of VCO with adsorbent zeolite was proven to reduce water content and free fatty acid levels with the highest percentage decrease in water content by 66%, and the highest percentage decrease in free fatty acid 63%. From the results of the study it can be concluded that the addition of pineapple stem extract containing the enzyme bromelain in the production of VCO can increase the yield of VCO to a maximum of 35.9% and purification of VCO samples with adsorbent zeolite proven to help reduce water content and free fatty acid levels.